Snakebite in Bangladesh: A Hidden Public Health Concern - Rahman, Md Motlabur; Mostafi, Mamun (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract not available J Bangladesh Coll Phys Surg 2024; 42: 301-302